Promoting Road Safety for Sustainable Communities: Analysing Driving Anger, Aggressive Driving, and Road Accident Proneness with Partial Least Squares Structural Equation Modelling (PLS-SEM) Approach - Mohd Kassim, Muhammad Asyraf; Abdul Hanan, Suhaila; Abdullah, Muhammad Safizal; Yusof, Mohd Faizal; Mansor, Mohd Fitri; Mohd Nawi, Mohd Nasrun; Mat Junoh, Mohd Zukime (FACMED - Faculty of Medical and Juridical Sciences, 2023)
Objective: Numerous studies have emphasized the web of factors contributing to a driver’s vulnerability to road accidents. These factors often stem from the interaction between drivers’ conduct, environmental conditions, and vehicle-related aspects. Among these elements, road rage and aggressive driving behavior are particularly noteworthy for their roles in road accidents. In this article, we delve into the connection between road rage, aggressive driving, and their combined impact on the likelihood of road accidents among Malaysian drivers. Theoretical framework: Theoretical materials were based on international scientific publications, reports, and scientific papers. Empirical findings from previous studies were critically reviewed for a more complete and objective presentation of the road accident problem. Methodology: This study used a cross-sectional design to administer self-administered questionnaires to drivers. The survey method made it possible to study the factors influencing susceptibility to traffic accidents quantitatively. The analysis reveals compelling insights using a rigorous structural equation modeling approach. Results and Conclusion: Driving anger and aggressive driving significantly influence the likelihood of road accidents among Malaysian drivers. This study holds significant implications for theoretical understanding and practical intervention strategies to reduce road accident proneness within the Malaysian road user community. The findings provide valuable insights and recommendations to enhance road safety, ultimately contributing to the sustainability of communities through reduced road accidents. Originality/value: The originality and value of the study lie in its in-depth examination of the relationship between driving anger, aggressive driving, and the likelihood of road accidents among Malaysian drivers. It goes beyond existing research by employing a rigorous structural equation modelling approach, drawing from international scientific publications and empirical findings. This comprehensive approach offers fresh insights into the specific context of Malaysia and provides a foundation for practical interventions to reduce road accident proneness, contributing to community sustainability and road safet